PEDAGOGICAL AND PSYCHOLOGICAL FOUNDATIONS OF INTEGRATION OF MODERN PRIMARY EDUCATION LESSONS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article talks about pedagogical and psychological foundations of integration of modern primary education lessons. They combine different systems of knowledge, provide an opportunity to know the diversity of the phenomenon or process. Based on this knowledge, general concepts arise.